Gambaran Pelayanan Kebidanan Komplementer di PMB Kota Surabaya - Aryunani Aryunani (Jurnal Keperawatan Muhammadiyah, 2020)
Objective: This study aimed to identify complementary midwifery services provided by midwives at the Surabaya City Midwife Independent Practice.Methods: The research method used in this study is a survey. The population in this study was all patients who were complementary to the samples used were 20 midwives in the IBI area of Surabaya City with sampling techniques using purposive sampling in March 2020. The measuring instrument in this study uses a questionnaire that the researcher himself has made. Data collection in this study was carried out using questionnaires/ questionnaires. The data of the research results were analysed using quantitative descriptive analysis.Results: The study was conducted on 20 midwives in the IBI area of Surabaya City. All respondents provided massage services to mothers and babies as much as 100%, as many as 18% (13 midwives) provided hypnotherapy services, 21% performed yoga services, 22% provided aromatherapy services and 11% provided acupressure services to pregnant women.Conclusion: of the 20 respondents, all have performed complementary obstetrics services that are also in demand by consumers.